Hyoid fracture concomitant with comminuted mandibular fracture: A case report. Issue 6 (November 2021) - Ito, Yu; Abe, Atsushi; Katayama, Yoshiko; Adachi, Moriyasu
Abstract: In rare cases, traumatic injury of the maxillofacial area may cause a hyoid fracture. We treated a rare case of hyoid fracture accompanying comminuted mandibular fracture. A 71-year-old man who fell from scaffolding at a height of 2 m was transported by ambulance to our facility. The patient was diagnosed with mandibular comminuted fracture and hyoid fracture based on computed tomography imaging. Open reduction and internal fixation were performed on the mandibular comminuted fracture. We selected conservative treatment for the hyoid fracture as it was only causing mild odynophagia and laryngeal edema. The patient did not exhibit any dyspnea, subcutaneous emphysema, or bloody sputum. On day 4 of hospitalization, the laryngeal edema and odynophagia had improved. On day 28 of hospitalization, the patient was discharged after progressing favorably postoperatively. At 6 months postoperatively, computed tomography images showed that although the greater horn of hyoid bone had not returned to its proper position, deviation had improved compared to that before surgery, and continuity was confirmed with the cortical bone. Repositioning and osteosynthesis of the mandibular fracture were favorable. In cases of maxillofacial trauma exhibiting laryngeal trauma injuries such as hyoid fracture, even mild cases have a risk of developing serious dyspnea over time. Physicians should consider carefully monitoring the course of such cases over 48–72 h. The possibility of relatively rare concomitant injuries such as hyoid fracture needs to be taken into account when diagnosing and treating maxillofacial trauma cases.